Responses to structural violence: The everyday ways in which queer and trans migrants with precarious status respond to and resist the Canadian immigration regime - Edward Ou Jin Lee (International Journal of Child, Youth & Family Studies, 2019)
This article examines how the Canadian immigration regime socially organizes the everyday lives of queer and trans migrants with precarious status. Drawing from key findings from an institutional ethnographic study, this article maps out the disjuncture between the actual experiences of queer and trans migrants with precarious status and the ideological and textual production of precarious status by the Canadian state. Making explicit this disjuncture reveals how the Canadian immigration regime enacts structural violence upon queer and trans migrants. This article also engages with the response-based approach to violence in order to understand how queer and trans migrants actively respond to this violence. In doing so, this article highlights the ways in which queer and trans migrants respond and resist the structural violence integral to the Canadian state’s production of precarious status.
Keywords: LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; identités LGBTQIA2+; immigration; pol4212; premier cycle; queer; ressource en ligne; régions géographiques; thématiques; transféminisme; violences

Trans*: A quick and quirky account of gender variability - Halberstam, Jack (American studies now : critical histories of the present, 2018)
In the last decade, public discussions of transgender issues have increased exponentially. However, with this increased visibility has come not just power, but regulation, both in favor of and against trans people. What was once regarded as an unusual or even unfortunate disorder has become an accepted articulation of gendered embodiment as well as a new site for political activism and political recognition. What happened in the last few decades to prompt such an extensive rethinking of our understanding of gendered embodiment? How did a stigmatized identity become so central to U.S. and European articulations of self? And how have people responded to the new definitions and understanding of sex and the gendered body? In Trans*, Jack Halberstam explores these recent shifts in the meaning of the gendered body and representation, and explores the possibilities of a nongendered, gender-optional, or gender-queer future.
Keywords: approches et analyses; corps; cours; fem3200; identités LGBTQIA2+; personnes trans*; premier cycle; queer; ressource en ligne; thématiques; transféminisme

91-LGBT+ - Babin, Sylvette; Glenn, Clinton; Gayed, Andrew; Barbu, Adam; Williamson, Andrea; Varghese, Ricky; Flavelle, Genevieve (2017)
Dans la foulée du numéro précédent, qui portait sur les féminismes, ce dossier poursuit la réflexion sur la question des genres et des sexualités en s’attardant aux pratiques et aux théories qui cherchent à transcender la pensée binaire de la société patriarcale hétéronormative et cisnormative. On y explore notamment les stratégies déployées par les artistes afin de rendre visible les communautés LGBT+ et de faire entendre la multiplicité des voix en marge du régime patriarcal de production des savoirs.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; arts; arts visuels et médiatiques; canada; corps; cours; discipline; har4600; histoire de l'art; hétérosexisme; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; transféminisme

Pour des interventions anti-oppressives auprès des jeunes trans: nécessités sociales, évidences scientifiques et recommandations issues de la pratique - Medico, Denise; Pullen-Sansfaçon, Annie (Service social, 2017)
Depuis 2011, de plus en plus d’études documentent les besoins et enjeux des jeunes et des enfants qui se sentent différent.e.s dans leur genre. S’il en ressort qu’illes sont encore parmi les jeunes les plus à risque de suicide, de violence par les pairs, d’échec scolaire, de dépression, d’anxiété et de troubles alimentaires, un milieu de vie qui les accepte et les soutient semble le facteur le plus déterminant pour leur santé tant psychique que relationnelle et somatique et leur insertion sociale et professionnelle. Pour favoriser un développement harmonieux pour les jeunes trans et en questionnement, une perspective anti-oppressive est aujourd’hui nécessaire.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; transféminisme; travail social; trs1205; violences

Se retrouver entre soi pour se reconnaitre: conceptions du genre et regulation des echanges dans un forum de personnes trans - Pastinelli, Madeleine; Dery, Caroline (Anthropologie et Societes, 2016)
Les possibilités de communication anonyme permises par les nouvelles technologies amènent des personnes qui ont en commun des pratiques ou des expériences qui les stigmatisent à se retrouver à l’abri des regards pour échanger entre elles et former des communautés en ligne. Ce faisant, elles se réapproprient leur expérience dans un langage choisi qui leur permet de redonner sens à des identités et des pratiques marginales ou considérées comme déviantes ou pensées comme relevant de la pathologie par le discours médical. L’enquête que nous avons menée dans une communauté en ligne de personnes trans éclaire la manière dont la fréquentation de celle-ci permet à ces personnes de se (re)connaître dans leur expérience particulière du corps et du genre et de faire sens de cette expérience. La volonté communément partagée par ces personnes de penser autrement leur expérience donne lieu à la rencontre d’une multitude de conceptions différentes, et parfois incompatibles entre elles, de l’identité de genre et de l’expérience trans. L’analyse se penche plus particulièrement sur la régulation du discours et des échanges qui est faite par les modérateurs dans ce contexte et sur le type de consensus qu’elle rend possible.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; outils; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; transféminisme

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Debates in transgender, queer, and feminist theory: contested sites - Elliot, Patricia (Queer interventions, 2010)
Intersecting the domains of women's studies, sexuality, gender and transgender studies, Debates in Transgender, Queer, and Feminist Theory provides a critical analysis of key texts and theories, engaging in a dialogue with prominent theorists of transgendered identity, embodiment and sexual politics, and intervening in various aspects of a conceptually and politically difficult terrain.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; identités LGBTQIA2+; lit4700; premier cycle; ressource en ligne; sciences humaines; sociologie; thématiques; transféminisme